The Role of a Nurse in Preventing Patient Falls in Dialysis Unit (Literature Review) - Akhmad Husairi; Ahyar Wahyudi (PT FORMOSA CENDEKIA GLOBAL, 2023)
Hemodialysis is a medical procedure aimed at replacing the kidney's function in filtering waste and excess fluid in the patient's blood. This article discusses the role of nurses in preventing patient falls. The purpose of this writing is to explore the crucial role played by nurses in ensuring patient safety during hemodialysis procedures and how this role becomes a critical focus in the supervision and evaluation by accreditation surveyors in the context of healthcare services. The writing method employs a literature review, and the discussion is conducted with various theoretical reviews and experiences regarding the importance of preventing patient falls. From this article, we can conclude that the nurse's role is crucial in providing nursing care to prevent patient falls.